Pembuatan sol karet lembaran untuk sandal - Herminiwati, Herminiwati; Karsiati, Niken (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1999)
The purpose of the research was to find best formulation for rubber sole sheeting for sandal. The formulation of the compounds were made by variation ratio of natural rubber and sintetic rubber SBR as follow : 100/0, 75/25, 50/50, 25/75 and 0/100, where as the variation ratio of carbon black N330 and aluminium silicate filler 100/0, 60/40 and 20/80 respectively. Compounding process was carried out on two roll mill.The rubber compounds were vulcanized at temperature 150oC and pressure of 150 kg/cm2 with curing time as indicated by curometer. Vulcanized rubber were tested based on SNI. 06-0899-1989 : Rubber sheeting for sole. The best formulation was consist of natural rubber 75 phr, sintetic rubber SBR 25 phr, stearic acid 3 phr, zinc oxide 5 phr, Minarex B oil 5 phr, car bon black 100 phr, MBTS 1 phr, PBN 1 phr and sulfur 2 phr. The physical properties of the best compound were : tensile strength 185,42 kg/cm2, elongation at break 276,64%, tear resistance 158,90 kg/cm2, hardness 74 shore A, density 1,21 g/cm3, Grasselli abrasion resistance 0,326 mm3/kgm, permanent set 7,78% and no crack on the flex cracking test. The best compound could meet the requirements of SNI. 06-0899-1989. INTISARI Penelitian ini bertujuan untuk mendapatkan formulasi terbaik dalam pembuatan sol karet lembaran untuk sandal. Formulasi kompon dibuat dengan variasi perbandingan karet alamdan karet sintetis SBR sebagai berikut : 100/0, 75/25, 50/50, 25/25 dan 0/100, sedang variasi perbandingan filler carbon black dan aluminium silikat berturut-turut 100/0, 60/40, dan 20/80. Proses komponding dilakukan dengan alat two roll mill, kompon karet divulkanisasi pada suhu 150oC, tekanan 150 kg/cm2 dan waktu vulkanisasi sesuai dengan waktu pada curometer. Vulkanisat karet diuji menurut SNI. 06-0899-1989 : Lembaran karet cetak untuk sol. Formulasi terbaik terdiri atas karet alam 75 phr, karet sintetik SBR 25 phr, asam stearat 3 phr, Zn O 5 phr, minyak Minarek B 5 phr, carbon black 100 phr, MBTS 1 phr, PBN 1 phr dan sulfur 2 phr. Sifat fisis formulasi terbaik adalah : tegangan putus 185,42 kg/cm2, perpanjangan putus 276,64%, ketahanan sobek 158,90 kg/cm2, kekerasan 74 shore A, bobot jenis 1,21 g/cm3, ketahanan kikis Grasselli 0,326 mm3/kgm, perpanjangan tetap 7,8% dan tidak retak pada uji ketahanan retak lentur, serta memenuhi persyaratan SNI. 06-08991989.